ETIKA PROFETIK DALAM NOVEL RANAH 3 WARNA KARYA AHMAD FUADI - Nimas Amalia Ulfa; Ahmad Rabi’ul Muzammil; Agus Wartiningsih (Universitas Tanjungpura, 2022)
Prophetic Ethics in the Ranah 3 Warna novel by Ahmad Fuadi. Indonesian Language Education Study Program, Department of Language and Arts Education, Faculty of Teacher Training and Education, Tanjungpura University, Pontianak. The first advisor is Drs. Ahmad Rabi'ul Muzammil, M.Si. and the second advisor is Dr. Agus Wartiningsih, M.Pd. This study examines the prophetic values in the Ranah 3 Warna novel by Ahmad Fuadi. This study aims to figure out objectively about three things. Those are humanization, liberation, and transcendent. The method used in this research is Library Research in the form of qualitative research. The data source in this study is the text in Ranah 3 Warna novel by Ahmad Fuadi, published by PT Gramedia Pustaka Utama. The technique that is used for data collection is an indirect technique with a documentation study. The tools for data collection are writing instruments and a list of notes. The results of the analysis are as follows: The form of humanization ethics (Amar Maruf), liberation ethics (Al-Munkar), and transcendence ethics (Tuminuma Billah). The results of this study can support the Indonesian language learning process about novel texts on the school XII class level or the equivalents in the even semester.